How Costly Is It For Poor Farmers To Lift Themselves Out of Poverty? - Olarreaga, Marcelo 1996- (The World Bank, 2006)
The main objective of this paper is to provide estimates of the cost of moving out of subsistence for Madagascar's farmers. The analysis is based on a simple asset-return model of occupational choice. Estimates suggest that the entry (sunk) cost associated with moving out of subsistence can be quite large - somewhere between 124 and 153 percent of a subsistence farmer's annual production. Our results make it possible to identify farm characteristics likely to generate large gains, if moved out of subsistence, yielding useful information for the targeting of trade-adjustment assistance programs